1996
DOI: 10.1111/j.1432-1033.1996.0295n.x
|View full text |Cite
|
Sign up to set email alerts
|

Human Bone Morphogenetic Protein 2 Contains a Heparin‐Binding Site which Modifies Its Biological Activity

Abstract: Bone morphogenetic protein 2 (BMP-2) plays a decisive role during bone regeneration and repair as well as during various stages of embryonal development. A cDNA encoding mature human BMP-2 could be efficiently expressed in Esclzerichia coli, and after renaturation a dimeric BMP-2 protein of M , 26000 was prepared with a purity greater 98 %. The recombinant BMP-2 was functionally active as demonstrated by the induction of alkaline phosphatase activity in the C3HlOT1/2 fibroblast cell line (EC,, of 70 nM) and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
454
2
8

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 523 publications
(482 citation statements)
references
References 70 publications
18
454
2
8
Order By: Relevance
“…One possible solution to this problem is high-efficiency, lowcost production of monomer rhBMPs in BMP-gene-transfected E. coli and conversion of the monomer rhBMPs to dimeric rhBMP using ex vivo biochemical processing. The ectopic induction of new bone formation by dimeric E-BMP-2 has already been reported elsewhere [22,32]. Recent studies in our laboratory found that characteristics of E-BMP-2 are satisfactory for clinical use to promote bone healing in place of the currently available BMP-2 produced by BMP-2-expressing CHO cells [12,43].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…One possible solution to this problem is high-efficiency, lowcost production of monomer rhBMPs in BMP-gene-transfected E. coli and conversion of the monomer rhBMPs to dimeric rhBMP using ex vivo biochemical processing. The ectopic induction of new bone formation by dimeric E-BMP-2 has already been reported elsewhere [22,32]. Recent studies in our laboratory found that characteristics of E-BMP-2 are satisfactory for clinical use to promote bone healing in place of the currently available BMP-2 produced by BMP-2-expressing CHO cells [12,43].…”
Section: Discussionsupporting
confidence: 54%
“…Dimeric E-BMP-2 was purified using several steps of chromatography. Details of the procedures for dimerization of cytokines have already been reported [12,32,42,43].…”
Section: Rhbmp-2mentioning
confidence: 99%
“…HS has been implicated in facilitating and stabilising the interaction of FGFs with their receptors. The more complicated interaction with BMPs have been demonstrated to include a stabilizing and storage role in the extracellular space (Ruppert et al 1996), maintaining the growth factor spatially away from it's receptor, thus limiting signaling potential (Takeda et al 2003) and preventing diffusion from a site of injury (Depprich et al 2005), however these interactions act in unison to modulate the activity and it has not yet been shown that HS interacts directly with the BMP2/receptor complex. Nontheless, a synergistic interaction seems apparent between HS and BMP2, although the exact mechanism driving this is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps, but a more likely explanation is that the biological significance of the interactions of these growth factors with HS is simply not captured by the kinds of in vitro assays that are typically used to study growth factor signaling. Support for this idea has come from genetic analysis of PG core protein mutants in vivo, in which HSPGs appear to regulate signaling by growth factors, such as members of the BMP family, and components of the insulin-like growth factor pathway (Pilia et al, 1996;Jackson et al, 1997), which in vitro assays have suggested are not HS-dependent (e.g., Ruppert et al, 1996).…”
Section: Rotes Of Pgs In Growth Factor Signatingmentioning
confidence: 99%